Dopaminergic and non-dopaminergic gait components assessed by instrumented timed up and go test in Parkinson’s disease - Dibilio, Valeria; Nicoletti, Alessandra; Mostile, Giovanni; Toscano, Simona; Luca, Antonina; Raciti, Loredana; Sciacca, Giorgia; Vasta, Rosario; Cicero, Calogero Edoardo; Contrafatto, Donatella; Zappia, Mario (Journal of Neural Transmission, 2017)
The timed up and go test (TUG) is a widely used clinical test for the evaluation of balance and mobility. An instrumented version of TUG (iTUG) has been proposed to provide quantitative information on TUG performances. Here, we hypothesized that l -dopa may differently influence gait parameters recorded by a portable inertial sensor. To test this idea, we evaluated iTUG test in patients with Parkinson’s disease (PD), both in l -dopa OFF and ON state. Twenty-eight PD patients performed the iTUG. Subjects were instructed to perform the task both in practical “OFF” and “ON” state. The system differentiated the test in six phases, recording phase durations, three-axial accelerations, average and peak angular speeds during turning. In all patients, sit-to-stand vertical and medio-lateral accelerations together with turning phase duration and angular speeds improved after l -dopa administration, while sit-to-stand and stand-to-sit phases antero-posterior accelerations were less responsive. In PD, l -dopa modulates iTUG in different ways, mostly improving the turning phases and less acting on postural controls during the sit-to-stand and stand-to-sit phases. Our results suggest different involvement of dopaminergic mechanisms on gait as assessed by iTUG. This is important for those aspects which are not improved by pharmacological therapy.